DI-059 Use, effectiveness and safety of ivabradine in paediatric patients. (24th February 2014) - Marquínez-Alonso, I; Manrique-Rodríguez, S; Fernández-Llamazares, CM; Ribed, A; Buendía-Bravo, S; Arrabal-Durán, P; García-González, X; Tovar-Pozo, M; Sanjurjo-Sáez, M
Abstract : Background: Ivabradine is authorised for the treatment of coronary artery disease and chronic heart failure with systolic dysfunction in adult patients, but there is little information on its efficacy and safety in children. Purpose: To assess the use, efficacy and safety of ivabradine in paediatric patients. Materials and methods: Observational study of the children treated with ivabradine in a university tertiary hospital. Patients' clinical records were reviewed and the following data were collected: date of birth, sex, weight, diagnosis and concomitant conditions, treatment duration and ivabradine dosing. Heart rate was used to assess effectiveness. Treatment was considered effective if the heart rate decreased below 130 bpm. Safety was assessed by the occurrence of any adverse events described in the summary of product characteristics. Results: Four children were treated with ivabradine in our institution, all of them for the indication of inappropriate sinus tachycardia as an off-label use. The median age at the start of treatment was 5.6 years (1.1–15.5). Three patients had undergone a heart transplant before treatment and the fourth started ivabradine before he had received a heart transplant. Median starting dose was 0.08 mg/kg/12 h (0.05–0.14). Median heart rate before treatment was 155 bpm (140–160). Ivabradine was effective for three patients, with a median of 110 bpm (110–128) after treatment, though one of them was considered a partial responder because the dose had to be doubled to maintain the desired heart rate. Treatment was ineffective for the remaining patient (median heart rate 147 bpm) and was discontinued. Overall, ivabradine was well tolerated. However, the dose had to be reduced to a half in one patient due to QT prolongation but was normalised after dose adjustment. Conclusions: Ivabradine seemed to be an effective and safe treatment for inappropriate sinus tachycardia in most of our paediatric patients. Nonetheless, more studies are required to confirm these results. No conflict of interest.